Experimenting With Computer-Assisted Interpreter Training Tools For The Development Of Self-Assessment Skills: National Parliament Of Rsa - Deysel, Elizabeth; Lesch, Harold (My University, 2018)
This article explores the use of cait as a tool in the development of self-assessment skills in interpreting performance. The aim of this pilot study is to investigate and evaluate the effectiveness of the cait software in the development of self-assessment skills of practicing interpreters in the National Parliament of the Republic of South Africa. The results indicate that the practicing interpreters which were exposed to the software displayed an improvement in their self-assessment skills and they indicated a better understanding of the criteria which are important in the assessment of interpreting performance as well as a better awareness of the strengths and weaknesses in the interpreters’ interpreting performance. The study concludes that cait may prove a viable tool also for in-house training and development of self-assessment skills of professional interpreters.
Keywords: South Africa; National Parliament; cait